How many ryanodine binding sites are involved in caffeine induced calcium release from sarcoplasmic reticulum terminal cysternae Vesicles? - Hasselbach, Wilhelm; Migala, Andrea (Zeitschrift für Naturforschung. C, a journal of biosciences, 1992)
The inhibition by ryanodine of caffeine induced calcium release from actively loaded heavy sarcoplasmic vesicles has been studied in order to analyse the relation between the occupancy of the vesicular calcium release channels by ryanodine and channel function. Ryanodine binding was monitored with [ 3 H]ryanodine under ionic conditions favouring the establishment of binding equilibrium. Binding follows 1 : 1 stoichiometry yielding dissociations constants between 7 - 12 nᴍ and 12-15 pmol ryanodine/mg vesicular protein as maximum number of ryanodine binding sites. When ryanodine labeling was monitored by measuring the decline of the amplitude of caffeine induced calcium release 50% inhibition occurred at a free ryanodine concentration of 1 nM. At this concentration less than 10% of the available ryanodine binding sites are occupied. Caffeine induced calcium release is completely abolished when 3 pmol ryanodine/mg have reacted. A corresponding divergence between ryanodine binding and its effect on caffeine induced calcium release was observed when the initial rate of ryanodine binding was measured either by labeling the vesicles with [ 3 H]ryanodine or by following the decline with time of caffeine induced calcium release. Caffein induced calcium release declines four times faster than the fraction of unoccupied ryanodine binding sites, k = 4.3 x 10 4 ᴍ -1 s -1 versus 1.2 x 10 4 ᴍ -1 s -1 . The observed interrelation between the occupation of ryanodine binding sites and its effect on caffeine induced calcium release indicates that the caffeine sensitive calcium channel functions as an assembly of at least 4 ryanodine binding sites whereby the occupation of one site suffices to abolish calcium release. The stoichiometric composition appears to be not fixed but might change according to the size of the fraction of ryanodine receptors exhibiting caffeine sensitivity. The reported data were evaluated according to the algorithm derived by H. Asai and M. F. Morales, J. Biol. Chem. 4, 830-838 (1965) for the activity of a macromolecule and the extent of an inhibiting reaction.
Elektronische Reproduktion der Druck-Ausgabe 2. Juni 2014
Gesehen am 21.07.2025